The assessment of material application through timber traditional Malay house construction - Priscilla Serimah, Bundan (2011)
In this paper, the construction of the traditional house has been influenced by the iterative adoptions to local conditions such as religion, climate and materials. Within the Peninsular of Malaysia, there exist three distinct regions - northern, central and eastern, in which the traditional differs in styles. In east Malaysia, the traditional houses are different since the communities there lives in one house that shared by more than one family. However, since the regions are subjected to almost similar local conditions, it is therefore not surprising to find the similarity of shape in most of these houses. This paper attempts to study the material application and construction through timber. There is much type of timber used in construction of traditional houses and the way it is build is most unique. Most of the material used is readily available local material such as timber, bamboo and many more. The study was conducted in Paloh Hinai, Pahang, Seremban, Negeri Sembilan and Miri Sarawak. And the study was carried out through case study and interviews. Then the data analysis was carried out.